INTEGRASI KURIKULUM AKADEMIK DENGAN KURIKULUM AGAMA DALAM MENDUKUNG KOMPETENSI HOLISTIK SISWA DI RUNGROTE WITTAYA SCHOOL CHANA, SONGKHLA, THAILAND. - Afandi, Ahmad; W, Dhevin M.Q Agus Puspita (STKIP Pesisir Selatan, 2025)
Rungrote Wittaya School in Thailand is one of the leading Islamic schools located in Chana, Songkhla, Southern Thailand. The school implements two main curricula: the academic curriculum (Saman) and the religious curriculum (Sassanah). Although both curricula are regulated by the Thai government, the school has the flexibility to develop the religious curriculum based on local needs. This article examines how the integration of academic and religious curricula supports the achievement of holistic competence among students. This study employs a qualitative method with a case study approach. Data collection techniques include observation, interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing. The results show that Rungrote Wittaya School implements curriculum integration using the shared model, connected model, threaded model, and immersed model. The curriculum is applied proportionally, with 60% allocated to the academic curriculum and 40% to the religious curriculum. The school also adopts a full-day school system and fosters a religious and nationalistic learning environment. These findings indicate that the integrated curriculum at Rungrote Wittaya School significantly contributes to shaping students with balanced cognitive, affective, and spiritual development.